Does CAP greening affect farms' economic and environmental performances? A regression discontinuity design analysis. (7th November 2022) - Varacca, Alessandro; Arata, Linda; Castellari, Elena; Sckokai, Paolo
Abstract: The Common Agricultural Policy reform 2013–2020 has conditioned 30 per cent of the direct payments to greening requirements. Our study investigates whether one of these requirements, the ecological focus area (EFA) obligation, has led to environmental improvements while preserving farms' economic sustainability. We apply a regression discontinuity design approach on a sample of Italian arable crop farms. Our results suggest that the EFA requirement has no significant effects on farms' application of fertilisers, pesticide expenditure, crop diversification or economic performance. However, farmers reacted to the EFA requirement by changing their crop mix, mostly by increasing their share of leguminous crops.